EFFECTIVITY OF STEM EDUCATION-BASED PHYSICS LEARNING E-MODULE INTEGRATED WITH CLIMATE CHANGE TOPIC TOWARDS STUDENTS’ COMPETENCE - Azfin Gustria; Ahmad Fauzi (Universitas Negeri Medan, 2020)
The effectiveness of e-learning modules is important to know the achievement of learning objectives. The aim of this study was investigating the effectivity of STEM Education based physcis learning e-module integrated with climate change topic towards students’ competence. Method that used in this research was quasi experiment whereas the sample’s were the eleventh grade students’ of SMA N 2 Sungai Penuh. Result of the experiment determined that e-module significantly effectives increasing students’ competence and environmental care. The implication of this research is e-module can be used as teaching materials on teaching process.